Analyzing the Trends of Paracetamol Overdose Toxicity in Mecca, Saudi Arabia: Implications for forensic analysis - Bandr Fakiha (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Acetaminophen poisoning is the commonest cause of poisoning worldwide and contributes to 30% of cases in Saudi Arabia. Pilgrimage seasons make it difficult for the city of Mecca to manage the specific issues related to medication abuse such as paracetamol overdose. This paper aims to analyse the rising incidence of Paracetamol poisoning in Mecca in comparison with other regions of KSA including during COVID-19 pandemic. Methodology: Cross-sectional retrospective record analysis was done using data obtained from the Ministry of Health (MOH) website on paracetamol overdose cases between years 2019 to 2020. Sociodemographic data, antidote use and outcomes data were obtained from the patient files on case record form and entered into Microsoft Excel spreadsheets. The analysis was based on the Paracetamol overdose incident in Mecca in relation to other areas. Results: Mecca’s overdose cases were 91 in 2019, but the numbers dropped to 28 in 2020. The spread per capita in people decreased from 1.00 per cent to 0.31 per cent in this period. This trend parallels a national decline, which appears to result from the COVID-19 pandemic and related limitations. Conclusion: The study’s results imply that measures attributable to the COVID 19 disease outbreak such as mobility restrictions and improved awareness of health concerns helped decrease cases of paracetamol overdose. Future studies should aim to investigate antecedent psychological, social, cultural factors and characteristics of overdose among users in Saudi Arabia.